Inhibitive effect of azine and diazine derivatives on the corrosion of 316L SS in acidic media - A.S. Fouda; Desoky A.M. El; A.A. Keshk (Zaštita Materijala)
The inhibiting effect of some azine and diazine derivatives on the corrosion of cyclic stressed 316L SS specimens in 3 M HCl in the presence of organic derivatives with concentrations (1×10-6 M - 11×10-6 M) at 30oC was studied using weight loss and galvanostatic polarization techniques. The inhibition of these derivatives on the uniform corrosion was evaluated by anodic and cathodic polarization curves of the electrode in the tested media. The examined derivatives exerted an inhibiting action towards corrosion. Polarization studies revealed that these derivatives behave as mixed inhibitors and inhibit corrosion by parallel adsorption on the specimen surface due to the presence of more than one active centre in the inhibitor molecule. The adsorption obeyed Temkin adsorption isotherm. The inhibitor efficiency increases with increasing the concentration of the inhibitor and decreases with increasing the value of the cyclic stress. Addition of I-, Br- and SCN- ions to the solution containing organic derivatives increases the inhibition efficiency of the system.